KERAGAAN VARIETAS PADI SAWAH IRIGASI DAN PENINGKATAN PENDAPATAN MELALUI PENDAMPINGAN PENGENDALIAN TANAMAN TERPADU (PTT) DI PROVINSI BALI - Sagung Ayu Nyoman Aryawati; Putu Sutami (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2019)
Performance of Irrigated Rice Varieties and Incresing t of Income Through ICM Assistance in Bali Province. Rice commodity assistance program is a strategic approach to increase rice productivity through Integrated Crop Management (ICM) to support sustainable agriculture. The study aimed to determine the agronomic performance of several high yielding varieties (HYVs) of rice and to increase farmers' income through mentoring programs ICM. The research was conducted using HYVs display locations in 9 districts/city in 2014 Bali Province. The study involved 45 respondents before and after ICM by taking 5 people from each regency/city using stratified random sampling method. The data of the collected agronomic components were analyzed using the diversity scheme (ANOVA). Costs and farm income were analyzed using analysis of income and financial feasibility. Agronomic performance of several high yielding varieties (HYVs) of rice on ICM mentoring program were different according to varieties and types of land agro-ecosystem. The analysis showed an increase in productivity with the implementation of ICM average of 1.30 tonnes/ha RHD increased by 24.82%. Rice farm income per hectare after ICM of 17.209.704,00 IDR and before ICM 12.644.656,00 IDR or increased 36.10%. The results of financial analysis indicated that the farming system was feasible to be developed with R/C after ICM of 2.94 and before ICM 2.53 or difference by 0.41. Rice farming is expected to implement ICM in order to support sustainable agriculture.Keywords: rice, ICM, high yielding varieties, incomeABSTRAK Program pendampingan komoditas padi merupakan pendekatan yang strategis dalam peningkatan produktivitas padi sawah melalui Pengelolaan Tanaman Terpadu (PTT) untuk mendukung pertanian berkelanjutan. Penelitian bertujuan mengetahui keragaan agronomis beberapa varietas unggul baru (VUB) padi sawah dan peningkatan pendapatan petani melalui program pendampingan PTT. Penelitian dilaksanakan pada lokasi display VUB di 9 kabupaten/kota Provinsi Balitahun 2014. Penelitian melibatkan 45 orang responden sebelum dan sesudah PTT dengan mengambil 5 orang masing-masing kabupaten/kota menggunakan metode stratified random sampling. Data komponen agronomis yang dikumpulkan dianalisis menggunakan sidik keragaman (ANOVA). Biaya dan pendapatan usahatanidianalisis menggunakan analisis pendapatan dan kelayakan finansial. Keragaan agronomis beberapa VUB padi sawah pada program pendampingan PTT berbeda menurut varietas dan tipe agroekosistem lahan. Hasil analisis menunjukkan peningkatan produktivitas dengan penerapan PTT rata-rata sebesar 1,30 ton/ha GKG atau meningkat 24,82%. Pendapatan usahatani padi sawah per hektar sesudah PTT sebesar Rp17.209.704 dan sebelum PTT sebesar Rp12.644.656 atau meningkat 36,10%. Hasil analisis finansial menunjukkan layak untuk dikembangkan dengan nilai R/C sesudah PTT sebesar 2,94 dan sebelum PTT 2,53 atau selisih 0,41. Usahatani padi diharapkan menerapkan PTT mendukung pertanian berkelanjutan. Kata kunci: padi, PTT, varietas unggul baru, pendapatan